2013
DOI: 10.1039/c3sc22215b
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved monitoring of dynamic self-assembly of Au(i)-thiolate coordination polymers

Abstract: Research interest in dynamic assemblies of coordination polymers (CPs) has been rising in recent years for the similarity with life systems in their self-adaptable morphologies and properties. However, monitoring of the assembly process and elucidating the nature for the morphological transformation are very challenging. Here, UV-Vis spectroscopy has been explored as a time-resolved method for monitoring the self-assembly of Au(I)-thiolate CPs in situ. Both step-wise and synergetic effects of the weak interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 41 publications
1
81
0
2
Order By: Relevance
“…ATCP nanosheets have well‐resolved sharp UV/Vis absorption peaks, which are suggested to result from ligand‐to‐metal charge‐transfer (LMCT) and metal‐centred charge‐transfer (MCCT) transitions ,,. The absorption peaks can be an indication of the formation of nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ATCP nanosheets have well‐resolved sharp UV/Vis absorption peaks, which are suggested to result from ligand‐to‐metal charge‐transfer (LMCT) and metal‐centred charge‐transfer (MCCT) transitions ,,. The absorption peaks can be an indication of the formation of nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…The above results show a non‐linear relationship between the rate of disappearance of nanosheets and the rate of generation of the gold nanoparticles, which suggest that the disappearance of nanosheets and generation of gold nanoparticles are two separate processes, and NaBH 4 may also play other roles besides as a reductant. Because our previous work has demonstrated that the Au I ‐MPA nanosheets are sensitive to pH value and show reversible assembly and disassembly behaviour on tuning the attraction and repulsion forces between MPA ligands, we turned our attention to the pH change after addition of NaBH 4 . The pH value rises from neutral and stabilizes at 9.8 because of the hydrolysis of NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solution color turned from yellow to brown, indicating that Au(III) ions were reduced to Au(0), forming CTAB‐capped Au nanoparticles or nanoclusters. After a controlled reaction time (typically ranging from 10 min to 40 h to form NPs of 2–8 nm in diameter), the Au NPs were etched for preparing Au(I)‐SR . 100 µL MPA was injected into the solution of preformed CTAB‐capped Au nanoparticles under stirring, and the solution then was incubated for 15 h under stirring to produce Au(I)‐thiolate species.…”
Section: Methodsmentioning
confidence: 99%